Sleeping Patterns, Personality Insights, and Emotional Savvy: A Study of Medical Students at Hang Tuah University in Surabaya - A. S. Ramadhina, Nurul Saqinah; Anindya Nugraheni, Pramita; Irawati, Ade; Pratama A., Ronald (Jurnal Psikiatri Surabaya, 2025)
Introduction: Adequate sleep is crucial for adolescent health because sleep deprivation can induce moodiness and frustration. Personality, encompassing introversion and extraversion, influences behavior and interaction patterns. Emotional intelligence pertains to the recognition and management of one’s own emotions and those of others. Methods: This study explored the relationships among sleep quality, personality type, and emotional intelligence among 5th and 7th semester students at the Faculty of Medicine, Hang Tuah University Surabaya, from 2024--2025. Using a descriptive analytic design and cross-sectional approach, 196 respondents were selected via purposive sampling. Data were collected via the Pittsburgh Sleep Quality Index, Personality Type Questionnaire, and Emotional Intelligence Questionnaire, which are distributed online. No personally identifiable information was collected, ensuring the full anonymity of the respondents. Results: Spearman’s correlation analysis revealed significant relationships between sleep quality and personality type (r = 0.235, p = 0.0005), between sleep quality and emotional intelligence (r = 0.212, p = 0.0005), and between personality type and emotional intelligence (r = 0.1476, p = 0.0005). Poor sleep quality was associated with lower emotional intelligence, indicating that sleep affects emotional awareness. Similarly, personality type was correlated with variations in emotional intelligence. Conclusion: This study revealed significant correlations between sleep quality, personality type, and emotional intelligence among medical students, suggesting that these factors play a key role in their emotional wellness.